NILAI KEARIFAN LOKAL DALAM KOMIK LEMBUSURA DAN RELEVANSINYA DENGAN PEMBELAJARAN SENI BUDAYA DI SEKOLAH MENENGAH PERTAMA - Swari, Raras Praba (SENADA (Seminar Nasional Manajemen, Desain dan Aplikasi Bisnis Teknologi), 2020)
ABSTRACT: Comics are pictorial media that contain sequential storylines. As one of the works of art, comics are often associated with modern adaptation art that is from a foreign culture and considered as reading that does not provide educational value. Lembusura Comic is one of the comics based on the local culture of East Java. The story in the comic contains the value of local wisdom and is closely related to the nation's cultural heritage. The value of local wisdom is considered true and maintained for generations in the community and can be used as a benchmark for controlling foreign cultures that influence the nation's culture and are not ensnared and forgotten. This study aimed to illustrate the value of local wisdom in the Lembusura comic that relevant to the study of art and culture in junior high school. Data obtained through library research methods. Data analysis used techniques with qualitative descriptive techniques. The results showed that the Lembusura comics contained several contents of the value of local wisdom they were, firstly, it could play a role in preserving Javanese culture, given the presentation of phenomena and comic character nuances of Javanese local wisdom, secondly, it contained the contents of advice, beliefs and prohibitions, third, meaningful for ethics and moral, fourth, social and fifth values ​​are values ​​of belief or divinity. This research can be used as a reference for preparing and planning arts and cultural studies in high schools and providing input in developing and implementing planning, implementation, and supervision models based on local wisdom. Keywords: local wisdom, comics, Lembusura, culture and art learning